Предмет: Алгебра, автор: slavasolyanin

tgX+ctgX=5 tg²X+ctg²X=?​

Ответы

Автор ответа: nelle987
1

Поскольку \mathop{\mathrm{tg}}x\mathop{\mathrm{ctg}}x=1, то

(\mathop{\mathrm{tg}}x+\mathop{\mathrm{ctg}}x)^2=\mathop{\mathrm{tg}}^2x+2\mathop{\mathrm{tg}}x\mathop{\mathrm{ctg}}x+\mathop{\mathrm{ctg}}^2x=\mathop{\mathrm{tg}}^2x+\mathop{\mathrm{ctg}}^2x+2

В данном случае

\mathop{\mathrm{tg}}^2x+\mathop{\mathrm{ctg}}^2x=(\mathop{\mathrm{tg}}x+\mathop{\mathrm{ctg}}x)^2-2=25-2=23

Похожие вопросы
Предмет: Математика, автор: lev958
Предмет: Математика, автор: мангл44